A molecular reappraisal of Abrothallus species growing on lichens of the order Peltigerales - Suija, Ave; de Los Ríos, Asunción; Pérez-Ortega, Sergio (Phytotaxa, 2015)
Species of the genus Abrothallus (Abrothallales, Dothideomycetes) are obligately lichenicolous (lichen-inhabiting) and grow on a wide variety of foliose and fruticose lichens. Bayesian Interference (BI) and Maximum Likelihood (ML) analyses of two gene loci—rDNA ITS and TEF-α—were used in order to infer the phylogenetic relationships among lineages of Abrothallus associated with hosts from the order Peltigerales (Lecanoromycetes). We found that the clade is subdivided into 13 lineages each of which can be delimited also by phenotypic criteria. Seven new species (Abrothallus boomii, A. canariensis, A. doliiformis, A. eriodermae, A. ertzii, A. etayoi and A. nephromatis) are described, two of which are known only by their asexual stage. Abrothallus welwitschii is lectotypified, and the original description is complemented. Vouauxiomyces brattii and Epinephroma kamchatica are combined within Abrothallus.